A Foreshock Bubble Driven by an IMF Tangential Discontinuity: 3D Global Hybrid Simulation. Issue 9 (7th May 2021) - Wang, Chih‐Ping; Wang, Xueyi; Liu, Terry Z.; Lin, Yu
Abstract: Foreshock bubbles (FBs) have been observed upstream of solar wind tangential discontinuities (TDs). A hypothesized mechanism is that foreshock ions with gyroradii larger than the TD thickness may move to upstream side of TDs and generate FBs. In this study, we present the very first three‐dimensional global hybrid simulation of an FB driven by a TD. After the TD encounters the ion foreshock, plasma and magnetic field perturbations are generated upstream of the TD. These perturbations are characteristically consistent with the observed TD‐driven FBs, confirming that TDs can form FBs. We further analyze the initial perpendicular temperature increase initiating the FB and compare the temperature structure with that from tracing test‐particles in static TD electric and magnetic fields. The structure can be explained by the perpendicular velocity change of foreshock ions with large gyroradii as they encounter the magnetic field direction change across the TD, which supports the hypothesized mechanism. Plain Language Summary: Foreshock bubbles (FBs) are one of foreshock transient phenomenon with large density, magnetic field, and flow perturbations. FBs were previously believed to be formed on the upstream side of interplanetary magnetic field (IMF) rotational discontinuity (RDs), but later they were also observed on the upstream side of IMF tangential discontinuities (TDs). Unlike RDs, there is no magnetic field connection between the two sides of a TD, so the open question is how foreshock ions can have access to the upstream side of a TD. A mechanism has been hypothesized to explain TD‐driven FBs. It proposed that energetic foreshock ions with gyroradii lager than the width of TDs may move to upstream side of TDs and generate FBs. However, this mechanism not been validated in realistic global simulations. In this study, we conducted the three‐dimensional global hybrid simulation to investigate this mechanism. Our simulation shows that an FB can be formed upstream of a TD, and the FB is initiated by a temperature increase contributing by energetic protons with large gyro‐radii moving across the TD. Thus, our simulation results validate the hypothesized mechanism. Key Points: A foreshock bubble (FB) formed upstream of a tangential discontinuity (TD) is simulated in 3D using the ANGIE3D hybrid code The FB is initiated by an increase of Ti, ⊥ upstream contributed by the foreshock ions with large gyroradii moving across the TD The Ti, ⊥ increase is due to the foreshock ion's v|| changing to v⊥ as they experience the magnetic field direction change across the TD